THE USAGE OF PHOSPHATE INHIBITORS AGAINST CORROSION OF EQUIPMENT IN THE OIL INDUSTRY - Niazbekova, A. B.; Salimova, D. K. (Ғылым және білім №2, 2020)
Protection of steel from negative effects with chemical reagents has been one very efficacious technique to enhance the endurance of production facilities and oil pipelines in invasive environments for a long time. The majority considerable damages were experienced by the heat power, water supply oil and gas industries. The application of inorganic inhibitors is a general practice in the mining industry in order to efficiently save steel in an invasive environment, in the existence of CO2 and H2S, due to the fact that corrosion inhibitors setback or decrease the impact of different factors on corrosion processes. The inhibitory method is characterized by high efficiency, low cost and ease of implementation. The use of inhibitors allows to avoid processing metal surfaces with protective enamels and mastics, and order expensive pipes made of alloy steel. In order to prevent corrosion, it is sufficient to place a chemical compound in an aggressive environment to neutralize or slow down the corrosion processes
Keywords: рк; научный журнал; периодическое издание; отечественное издание; химические реагенты; неорганические ингибиторы; химическое производство; corrosion; phosphates; inhibitor; oil industry; protection